Analisis Kebijakan Insentif Pajak Kendaraan Bermotor Dalam Meningkatkan Pendapatan Asli Daerah di Provinsi Nusa Tenggara Barat - Evva Junita Rahman; Muaidy Yasin; Ali Akbar Hidayat (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the Motor Vehicle Tax incentive policy based on the Governor of West Nusa Tenggara Regulation Number 9 of 2025 and its contribution to increasing Regional Original Revenue. This study uses a quantitative descriptive approach by utilizing secondary data from the Regional Revenue Management Agency of West Nusa Tenggara Province in 2025. Analysis techniques include income trend analysis, PKB contribution analysis to PAD, and elasticity analysis to measure the level of response of PAD to changes in PKB income before and after the incentive policy is implemented. The results of the study show that the PKB incentive policy is able to increase taxpayer compliance and encourage a significant increase in PKB revenue, especially in the early period of policy implementation. Although PKB's contribution to PAD is still in the